Perlindungan Hukum Atas Cerita Rakyat Yang Ditulis Oleh Pencipta Dalam Rangka Benefit Sharing - Kartika, Eva Dewi (UI Scholars Hub, 2018)
Indonesia is known as a country rich in culture. Every region in Indonesia has its own folklore that comes from the local community. This folklore is basically given through oral and non-written media and is known as folkore. Writing a book based on folklore with the inclusion of the name of the creator is not appropriate because the copyright of the folklore is included as one of the traditional cultural expressions and owned by the state, in this case managed and represented by the government. The community of origin of the folklore is also entitled to the utilization of the folklore, both in terms of moral rights and economic rights